Cluster-based time synchronisation scheme for femtocell network - Mohammad Kamrul, Hasan; Ahmad Fadil, Ismail; Hassan Abdalla Hashim, Aisha (Inderscience Enterprises Limited, 2015)
Femtocell is a recently developed technology in cellular wireless networks, which extends network coverage indoors, and is used to serve a small number of users. Synchronisation is one of the most significant technical challenges in femtocell networks and it guarantees an acceptable clock offset and frequency error (skew). Clock offset and skew lead to severe interference between femtocell base stations (fBSs) or between fBSs and macrocell base stations (mBSs). The ultimate objective of this paper is to develop cluster-based time synchronisation scheme to reduce clock offset and skew in terms of precise synchronisation in fBS neighbouring nodes. In consequence with the developed cluster-based time synchronisation scheme, the intra-cluster and inter-cluster time synchronisation is proposed. The proposed scheme is evaluated through analytical approach and benchmarked with mobile station-assisted synchronisation scheme. Results show that the proposed scheme is able to significantly reduce clock offsets to 53% and 60.32% for clock skew.